Islam and Terrorism: The Blurred Boundary Between the Cosmic and this World - Ochieng, Ahaya L. (Strathmore Law Journal, 2021)
Today the barbarity of crimes in the name of religion is all the more disturbing particularly when one considers the righteous religious language in which such heinous acts are cloaked. Violence perpetrated in the name of God continues to engage the world at alarming levels. It is in this regard that this study examines the general relationship between violence and religion in the specific context of Islam from the point of view of the cosmic war theory as advanced by Mark Juergensmeyer. The study observes that violent activities related to Islam are a result of the blurring of boundaries between the symbolic cosmic world of religion and this world, as a result of which the symbolic violence of religion translates into real violence. This translation is occasioned by violent groups in Islam legitimising their violence on the inherent symbolic violence of religions as they respond to ‘unfavourable’ local and global structural conditions.